Primary-Secondary wavelengths Spectrophotometric for improving the Determination of Nitrobenzene Compounds in wastewater - Gao, Hong-Wng (Asian Journal of Chemistry, 2010)
In acidic solution the conventional reaction of nitrobenzene with N-(1-naphthyl)-ethylendiamine-dihydrochloride (NEDA) in the presence of hydrazine sulfate and nitrite to form a red azo compound has been applied for the improvement of the determination of nitrobenzene compounds in water and wastewater by primary-secondary wavelengths spectrophotometry (PSWS). The updated method can bring out the higher precision and sensitivity than the ordinary spectrophotometry, but also the calculation model is stable. The result shows that the relative standard deviations were less than 2.1 % and the recovery rate of nitrobenzene between 96 and 104%. The detection limit of nitrobenzene was equal to 0.008 mg/L .